Visualizing a Living Building - Padget, Steve (ARCC Conference Repository, 2014)
This paper will chronicle the design process of the Odum School of Ecology at the University of Georgia and its objective to accomplish Living BuildingTM certification. In order to accomplish this, the architect (BNIM) and project partners applied Triple Bottom Line thinking, an Integrated Design Process and Life Cycle Analysis. The author, a member of the design team, will focus on the variety of representation techniques used and their roles within this design process pursuing Living BuildingTM status.